1982
DOI: 10.1021/i300008a013
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase polymerization of propene with the supported Ziegler catalyst: TiCl4/MgCl2/C6H5COOC2H5/Al(C2H5)3

Abstract: The gas-phase polymerization of propene with the MgCI,-supported Ti CI , / C, H, COOC, H, catalyst in conjunction with AI(C2H,), has been investigated. The rate of polymerization depends on both titanium content and surface area of the MgCITsupported catalyst and decreases with the polymerization time. The number of active centers in the catalyst at different polymerization times is estimated by the inhibition method using carbon monoxide. As a result, the number of active centers decreasesjuring the course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…This is reported for both slurry phase systems 14,15 and gas phase reactor systems. 30 Consequently, an experimental study focusing only on ethylene homopolymerization with different Al/Ti ratios was conducted. A reaction temperature of 50ЊC and a catalyst aging time of Ç 25 min were employed.…”
Section: Effect Of Al/ti Ratiomentioning
confidence: 99%
“…This is reported for both slurry phase systems 14,15 and gas phase reactor systems. 30 Consequently, an experimental study focusing only on ethylene homopolymerization with different Al/Ti ratios was conducted. A reaction temperature of 50ЊC and a catalyst aging time of Ç 25 min were employed.…”
Section: Effect Of Al/ti Ratiomentioning
confidence: 99%
“…Upon an increase of TEA concentration in the range of low concentration, the increase of activity might be attributed to the progressive activation of potential catalytic sites by interaction with TEA. 26 The decrease of the overall rate or increase of the decay rate for larger TEA concentration beyond certain limits might be due to the overreduction of titan i~m .~~…”
Section: Polymerization Conditionsmentioning
confidence: 99%
“…To observe the rate decay phenomenon, we carried out an interruption experiment similar to that performed by Doi et al 23 As shown in Figure 17, propylene was replaced by nitrogen during the polymerization, and, after about an hour of intermission, propylene was reintroduced to resume polymerization. Note that the rate decay seems to continue during the Note that the first-order decay law fits the reaction rate data very well and that the decay constant is not very sensitive to the [Al]/[Ti] ratio.…”
Section: Decay Of Polymerization Ratementioning
confidence: 99%